UJI MEKANIKA PAPAN PARTIKEL BERBAHAN DASAR KULIT SERABUT NIPAH (Nyfa fruticans Wurmb) DENGAN PEREKAT RESIN POLYESTER - Muhammad Ega Saputra; Rosidah -; Gusti Abdul Rahmat Thamrin (Jurnal Sylva Scienteae, 2021)
. In an effort to maximize the increase in economic value nipah plants, it is used to produce sugar, there also needs to be innovations that make nipah plants into high-value products, including the utilization of palm fiber for raw material for making particle boards. The objectives to be achieved in this research are Analyzing the mechanical properties of particle boards from palm oil with polyester resin adhesive. Particle board raw material used for palm fiber, The adhesive used is polyester resin by comparison A = 1:7, B = 1:8, C = 1:9. Static analysis of the data used is a completely randomized design (CRD) with three levels of treatment and three replications so the total number of trials is nine. The resulting density value includes medium density. Value of the resulting density in the treatment A (1:7), B (1:8), C (1:9) successively produce 0,78 gr/cm³, 0,69 gr/cm³, 0,62 gr/cm³. The average value of Modulus of Elasticity (MoE) The resulting effect is not real and does not meet SNI 03-2105-2006 min 20.400 kg/cm² except in the treatment A2, A3, B1, B3 that meets the standards SNI, Modulus of Rupture (MoR) The result has no real effect and the value produced meets SNI 03-2105-2006 for all treatments that require a minimum 82 kg/cm² in all treatments.Keywords: Particle Board; SNI 03-2105-2006; Polyester Resin; MoE; MoR